USE OF ULTRASONIC SENSOR BY DETECTING VEHICLE SAFE DISTANCE BASED ON ARDUINO UNO - Gregorius Advent Trisman Gaurifa; Muhammad Hanif Hidayatulloh, Paduloh (Adisam Publisher, 2024)
With the rapid growth of vehicles, improving road safety has become a necessity. Ultrasonic sensors provide an effective and efficient solution for measuring distance on vehicles, which can be implemented to improve traffic safety. Therefore, we need a system that can detect the distance between vehicles to make it safer. One way to detect a vehicle's safe distance is to use an ultrasonic sensor. An ultrasonic sensor is a tool that can detect a safe distance to a vehicle. This system is designed as an integration between Arduino Uno, ultrasonic sensors, and data processing algorithms. The Arduino Uno program was developed to control ultrasonic sensors, read distance data, and send alerts if potential risks are found. The implementation of the ultrasonic sensor on the Arduino Uno succeeded in proving its ability to detect safe distances between vehicles with high accuracy. By using the right algorithm, the system can provide early warning when a potential risk of collision is detected. Test results show a fast and reliable response from the system This research confirms the effectiveness of Arduino Uno-based ultrasonic sensors in improving traffic safety by detecting safe distances between vehicles.